The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1103/physrevb.103.094424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order in the quasi-one-dimensional Ising system RbCoCl3

Abstract: In RbCoCl 3 , the magnetic Co 2+ ions form weakly coupled Ising chains arranged on a triangular lattice. We have investigated the structure and magnetism in RbCoCl 3 by high-resolution x-ray diffraction and neutron scattering measurements on powder and single-crystal samples between 1.5 and 300 K. Upon cooling, the Co 2+ spins develop one-dimensional antiferromagnetic correlations along the chain axis (c axis) below 90 K. Below the first Néel temperature, T N1 = 28 K, a partial three-dimensional magnetic order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…1(b)], frustrating the AF interchain interactions. They typically show two magnetic ordering transitions, which in RbCoCl 3 occur at T N 1 = 28 K and T N 2 = 12 K [21]. Thus, in contrast to CoNb 2 O 6 and BaCo 2 V 2 O 8 , different chains experience different environments at different temperatures.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1(b)], frustrating the AF interchain interactions. They typically show two magnetic ordering transitions, which in RbCoCl 3 occur at T N 1 = 28 K and T N 2 = 12 K [21]. Thus, in contrast to CoNb 2 O 6 and BaCo 2 V 2 O 8 , different chains experience different environments at different temperatures.…”
mentioning
confidence: 99%
“…Three high-quality RbCoCl 3 single crystals of total mass 7.6 g were grown by the Bridgman technique in a moving vertical furnace [21] ter LET (ISIS, UK) [24]. High-statistics data were collected with incident energy E i = 25 meV and (00L) perpendicular to the incident beam, at temperatures of 4, 18, and 35 K, i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that a composite geometry consisted of Ising chains in a two-dimensional array can inherit the excellent traits of both geometries. For * zhiyingzhao@fjirsm.ac.cn example, in the S = 1/2 stacked Ising triangular lattice antiferromagnets (TAFs) ACoX 3 (A = Rb, Cs; X = Cl, Br) and Ca 3 Co 2 O 6 , in which Ising Co chains are arranged in a triangular lattice, not only the domain-wall excitations of one-dimensional antiferromagnetic (AFM) Ising chain [26,27], but also the magnetization plateau and partially disordered state in triangular lattice [28][29][30][31] are observed. Besides, a disordered ground state is also found in Ba 3 Co 2 O 6 (CO 3 ) 0.7 due to its honeycomb structure [32,33].…”
Section: Introductionmentioning
confidence: 99%